Air Quality Changes in Ukraine during the April 2020 Wildfire Event - Savenets, Mykhailo; Osadchyi, Volodymyr; Oreshchenko, Andrii; Pysarenko, Larysa (Geographica Pannonica, 2020)
The paper analyzes air quality changes in Ukraine during a wildfire event in April 2020 and a dust storm episode during the 16th of April 2020. The wildfire event contained two episodes of active fires and huge pollutants’ emission: 4–14 April and 16–21 April, respectively. Using the Sentinel-5P data of CO and NO2 column number density and ground-based measurements, there was estimated air quality deterioration. Advection of polluted air masses and analysis of affected territories were made in combination with a web-based HYSPLIT model. Satellite data described air quality changes better than in-situ measurements. Data intercomparison showed better coincidence in regions that were not affected by wildfire emissions. The paper described the dust storm event based on absorbing aerosol index (AAI) data that occurred between two wildfire episodes